Fluorescent sensors for ions based on organic structures - GUNNLAUGSSON, THORFINNUR (My University, 2010)
his report highlights some of the developments in 2009 of fluorescent, and in some cases, dual fluorescent and colorimetric, sensors, that are based on organic structures, and that were developed for the sensing/recognition of anions and cations.
PUBLISHED
Keywords: dual fluorescent and colorimetric, sensors; dual fluorescent and colorimetric, sensors